Effect of silver nanoparticles and silver ions on growth and adaptive response mechanisms of Pseudomonas putida mt‐2. Issue 1 (22nd May 2014) - Hachicho, Nancy; Hoffmann, Philipp; Ahlert, Kristin; Heipieper, Hermann J.
Abstract The distribution and use of nanoparticles increased rapidly during the last years, while the knowledge about mode of action, ecological tolerance and biodegradability of these chemicals is still insufficient. The effect of silver nanoparticles (AgNP) and free silver ions (Ag+, AgNO3) on Pseudomonas putida mt‐2 as one of the best described bacterial strains for stress response were investigated. The effective concentration (EC50) causing 50% growth inhibition for AgNP was about 250 mg L−1, whereas this was only 0.175 mg L−1 for AgNO3. However, when calculating the amount of free silver ions released from AgNP both tested compounds showed very similar results. Therefore, the antibacterial activity of AgNP can be explained and reduced, respectively, to the amount of silver ions released from the nanoparticles. Both tested compounds showed a strong activation of the unique membrane adaptive response of Pseudomonas strains, the cis‐trans isomerization of unsaturated fatty acids, whereas another important adaptive response of these bacteria, changes in cell surface hydrophobicity, measured as water contact angle, was not activated. These results are important informations for the estimation of environmental tolerance of newly developed, active ingredients like silver nanoparticles.